Pandemic, Human Security and Migration: Management of Human Mobility from Mexico - Hernández-López, Rafael-Alonso; Ramos, Diego Noel (FLACSO - Sede Ecuador, 2022)
Human mobility has become an extremely complex phenomenon in Mexico, especially the undocumented transit of people from Central American countries to the United States, due to changes in patterns, dynamics of flows and the response of the State. The objective of this article is to describe the main state policies of border and migration control in Mexico that have been consolidated in the last ten years. With a highly restrictive component, these policies have been based on securitization, displacing the relevance of human security. A critical analysis of the influences of the national security paradigm over the representation of migration as a threat in the context of the COVID-19 pandemic is presented. It is concluded that the pandemic allowed to justify the state’s indifference to people in an irregular situation in the country, but also to continue implementing immigration containment measures.